Efforts to Increase Students' Interest in Learning Fiqh Through Learning Media at MTs Muhammadiyah 13 Medan - Salsabila Salsabila; Hasrian Rudi Setiawan (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to enhance students' interest in learning Fiqh through the use of instructional media at MTs Muhammadiyah 13 Medan. The research employed classroom action research (CAR) methods consisting of two cycles, with each cycle involving planning, implementation, observation, and reflection phases. Data were collected through observation, interviews, and questionnaires. The findings revealed that the application of innovative learning media significantly improved students' learning interest. This was evidenced by the increased results of the learning interest questionnaire and students' active participation during the learning process. Thus, the appropriate use of instructional media can be an effective strategy to enhance students' interest in learning Fiqh.